KEEFEKTIFAN MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI WANTILGUNG BLORA - Eka Febrina Sisna Saputri; Choirul Huda; Singgih Adhi Prasetyo (Universitas Negeri Medan, 2018)
Abstract:. The Effectiveness of Two Stay Two Stray (Tsts) Learning Model Against Mathematics Learning Outcomes of Grade V Students of Wantilgung Blora Elementary School. This study aims to know and analyze the effectiveness of Two Stay Two Stray (TSTS) learning model to mathematics learning outcomes grade 5 SD Negeri Wantilgung Blora. This research type is quantitative research with True Experimental Design design that used is Pretest-Posttest Control Group Design. The population in this research is all students of class V SD Negeri Wantilgung Blora and SD Negeri Sambonganyar Blora. Based on theanalysis result of control class study and experimental class by using t test obtained tcount is bigger than ttable that is 4,852 > 1,9. Tcount > Ttable, the hypothesis is accepted. Learning by using Two Stay Two Stray (TSTS) model can improve student learning outcomes significantly, so effectively used in mathematics subjects SD Negeri Wantilgung Blora. Keyword : Effectiveness, Two Stay Two Stray (TSTS), Mathematics Learning Outcomes. Abstrak: Keefektifan Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Hasil Belajar Matematika Siswa Kelas V SD Negeri Wantilgung Blora. Penelitian ini bertujuan untuk mengetahui dan menganalisis keefektifan model pembelajaran Two Stay Two Stray (TSTS) terhadap hasil belajar matematika siswa kelas V SD Negeri Wantilgung Blora. Jenis penelitian ini adalah penelitian kuantitatif dengan bentuk True Experimental Design, yang digunakan adalah Pretest-Posttest Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas V SD Negeri Wantilgung Blora dan SD Negeri Sambonganyar Blora. Berdasarkan hasil analisis dari hasil belajar kelas kontrol dan kelas eksperimen dengan menggunakan uji T didapatkan thitung lebih besar dari ttabel yaitu 4,852 > 1,9. Jadi thitung > ttabel, sehingga hipotesis diterima. Pembelajaran dengan menggunakan model pembelajaran Two Stay Two Stray (TSTS) mampu meningkatkan hasil belajar siswa secara signifikan, sehingga efektif digunakan pada mata pelajaran matematika SD Negeri Wantilgung Blora. Kata Kunci : Keefektifan, Two Stay Two Stray (TSTS), Hasil Belajar Matematika.